Potent and Broad but not Unselective Cleavage of Cytokines and Chemokines by Human Neutrophil Elastase and Proteinase 3 - Fu, Zhirong (Int J Mol Sci, 2020)
In two recent studies we have shown that three of the most abundant human hematopoietic serine proteases—mast cell chymase, mast cell tryptase and neutrophil cathepsin G—show a highly selective cleavage of cytokines and chemokines with a strong preference for a few alarmins, including IL-18, TSLP and IL-33. To determine if this is a general pattern for many of the hematopoietic serine proteases we have analyzed the human neutrophil elastase (hNE) and human proteinase 3 (hPR-3) for their cleavage of a panel of 69 different human cytokines and chemokines. Our results showed that these two latter enzymes, in sharp contrast to the two previous, had a very potent and relatively unrestrictive cleavage on this panel of targets. Almost all of these proteins were cleaved and many of them were fully degraded. In light of the proteases abundance and their colocalization, it is likely that together they have a very potent degrading activity on almost any protein in the area of neutrophil activation and granule release, including both foreign bacterial or viral proteins as well as various self-proteins in the area of inflammation/infection. However, a few very interesting exceptions to this pattern were found indicating a high resistance to degradation of some cytokines and chemokines, including TNF-α, IL-5, M-CSF, Rantes, IL-8 and MCP-1. All of these are either important for monocyte-macrophage, neutrophil or eosinophil proliferation, recruitment and activation, suggesting that cytokines/chemokines and proteases may have coevolved to not block the recruitment of monocytes–macrophages, neutrophils and possibly eosinophils during an inflammatory response involving neutrophil activation.